Utilization of cassava peel waste (Manihot esculenta L.) with concentration variations of α-amylase and glucoamylase enzymes for liquid sugar - Rais Nur Latifah; Nur Rahma Martiyana (Jurnal Litbang Industri, 2023)
The production of liquid sugar utilizing cassava peel waste has been carried out in this study. The method used in the production of liquid sugar employs an enzymatic method. The stages in the enzymatic method are the liquefaction and saccharification processes. The liquefaction process involves the addition of α-amylase in varying amounts to break down starch into amylose and amylopectin. The saccharification stage aims to hydrolyze dextrins into liquid sugar using glucoamylase enzymes. The volumes of enzymes used were 0.2 mL and 0.6 mL. The research results indicate that the moisture content and ash content are in accordance with the Indonesian National Standard (SNI) 8779:2019, at 6.19% and 0.76%, respectively. Qualitative analysis of cassava peel starch shows positive results for amylum, dextrins, and glucose content. FTIR analysis of cassava peel starch reveals the presence of O-H groups, C-H groups, and C-O-C groups. Total Soluble Solid (TSS) testing for 0.2 mL and 0.6 mL enzyme volumes resulted in 12.56% and 17.37%, respectively. The optimum results for liquefaction and saccharification were observed with the addition of 0.2 mL enzyme volume. The functional groups of the liquid sugar were analyzed using FTIR, which showed the presence of O-H stretching, carbonyl groups (C=O), stretching vibration of C-OH, and vibration of glycosidic bonds C-O-C.